(untitled) (Brazilian Journal of Health Research, 2021)
Introduction: Population aging is one of the current greatest challenges faced by public health, since it increases social and economic demands. Because of the rising number of elderly individuals and the incidence of accidental falls in this population, femoral fractures stand out among the main traumatic lesions leading to hospitalizations, surgical treatment and even death in this population. Objective: Describing the epidemiological profile of femur fractures and death cases caused by accidental falls in elderly individuals living in Espírito Santo State, from 2010 to 2017. Methods: Ecological study based on secondary data collected from DATASUS database. Results: Most of the 6,521 femoral fracture cases observed in the elderly population during the investigated period affected women (66.7%), individuals with brown skin color (39.0%), and individuals in the age group 80 years or older (50.7%), who were treated in emergency services (82.5%) in the public health sector (43.3%); 353 patients have died. Individuals in the age group 80 years or older recorded lethality coefficient of 7.8%, those in the age group 70-79 years recorded 3.8% lethality, and elderly individuals in the age group 60-69 years recorded 1.8% lethality. Conclusion: Femoral fractures were mainly observed in female patients and they showed increasing lethality coefficient as patients got older. Such an information should be taken into consideration at the time to formulate public health policies and plan individual or group preventive actions focused on elderly individuals and on their families.